Peran Guru Pendidikan Agama Islam dalam Membentuk Karakter Religius di SMA Jati Agung Wage Sidoarjo : Penelitian - M Zam Zam; Yuliastutik; Hanik Yuni Alfiyah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Religious character is important to instill in students so they become perfect human beings with good morals. This study aims to determine the efforts of Islamic Religious Education (PAI) in fostering religious character at SMA Jati Agung Wage Sidoarjo. Although set in a public school, the religious atmosphere in this school is comparable to a madrasah, as seen in activities such as congregational prayer, BTQ (Quran Recitation), weekly fiqh studies, and the habit of giving alms. The formation of this character is inseparable from the role of PAI teachers. This study used a qualitative approach with thematic analysis through observation, interviews, and documentation. The results show that PAI teachers act as teachers, educators, guides, motivators, and evaluators. The religious character of students includes: obedience to worship, religious understanding, Islamic behavior, participation in religious activities, development of Islamic character, and commitment to Islamic values. Supporting factors include teacher competence and dedication, support from school leadership, active participation of the school community and parents, and adequate religious facilities. Barriers include time constraints, limited resources, student diversity, technological challenges, and evaluation demands.